Pengaruh Disiplin Kerja dan Pengawasan Terhadap Kinerja Petugas Biller di PT.PLN (Persero) ULP Lemah Abang - Mardiani, Inna Nisawati (Program Studi Manajemen Fakultas Ekonomi UST, 2024)
The purpose of this research is to find out whether work discipline and supervision of billing officers at PT. PLN (Persero) ULP Lemah Abang has influence or not. The methodology used in this research is quantitative. The data collection method was carried out by distributing questionnaires directly to 55 biller officers from PT. Haleyora Powerindo as a sample. Based on the test results of this research, work discipline and supervision have a positive and significant influence simultaneously on the performance of biller officers at PT PLN (Persero) ULP Lemah Abang.